2015
DOI: 10.1186/s40488-015-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Revisit of relationships and models for the Birnbaum-Saunders and inverse-Gaussian distributions

Abstract: The Birnbaum-Saunders distribution was derived in 1969 as a lifetime model for a specimen subjected to cyclic patterns of stresses and strains, and the ultimate failure of the specimen is assumed to be due to the growth of a dominant crack in the material. The inverse Gaussian distribution is used to describe the first passage time for a particle (moving with constant velocity) that is subject to linear Brownian motion. These two models have a rich history, and they have been shown to be much related. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The chief goal of our paper is to propose a log-linear regression model based on a bimodal version of the Birnbaum-Saunders distribution that has been recently introduced by Owen and Ng (2015). Such a distribution is more flexible than the original BS law and we use it as the basis for developing a regression model that is more general than the BSRM introduced by Rieck and Nedelman (1991).…”
Section: B J P S -Amentioning
confidence: 99%
See 2 more Smart Citations
“…The chief goal of our paper is to propose a log-linear regression model based on a bimodal version of the Birnbaum-Saunders distribution that has been recently introduced by Owen and Ng (2015). Such a distribution is more flexible than the original BS law and we use it as the basis for developing a regression model that is more general than the BSRM introduced by Rieck and Nedelman (1991).…”
Section: B J P S -Amentioning
confidence: 99%
“…They obtained it by adding a second shape parameter to the BS distribution function. More recently, Owen and Ng (2015) analyzed the distribution, which the authors denoted by GBS 2 . In particular, they investigated the relationships among the inverse Gaussian, BS and GBS 2 distributions.…”
Section: The Bimodal Birnbaum-saunders Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desmond observed that the hazard functions of the BS and IG distributions are very similar and came up with a similar conclusion as Bhattacharyya and Fries that the IG distribution is preferred for statistical analysis. For a detailed review of the relationships between the BS and IG distributions, one can refer to the work of Owen and Ng …”
Section: Fatigue Life Distributionsmentioning
confidence: 99%
“…Ref. [19] discussed the likelihood-based estimation of parameters and provided interval estimation based on "observed" Fisher's information. In this article, to contribute to the relatively neoteric body of research, we propose a new inference method for the parameter estimation and hypothesis testing for the GBS-II model.…”
Section: Introductionmentioning
confidence: 99%